Productivity Entrepreneurship for Alumnus Apprenticenship Kenshusei (Study Phenomenology Kenshusei Im Japan) (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this research is to describe the apprenticeship (means: Kenshusei in Japanese Language) program from Indonesia to Japan. This program has been started from 1992 between Indonesian Government, which was represented by Ministry of Labor Republic Indonesia, and Foreign Apprenticeship Institution Japan, IM Japan. The goal of this Apprenticeship program to Japan is to get transfer technology and to understand for all Japanese culture, which is the most famous culture are discipline and high work ethic. After finished, apprenticeship program, Kenshusei is hoped to return back home and build their own business. However, being an entrepreneur is not easy: how to increase entrepreneurship productivity level, how to understand about Japanese business culture and character for Process transfering knowledge to all apprenticeships will be research more deeply. The method used of this research is Qualitative, Phenomenology.